2007
DOI: 10.2147/ciia.2007.2.1.93
|View full text |Cite
|
Sign up to set email alerts
|

A review of a bi-layered living cell treatment (Apligraf�) in the treatment of venous leg ulcers and diabetic foot ulcers

Abstract: Apligraf® (Organogenesis, Canton, MA) is a bi-layered bioengineered skin substitute and was the first engineered skin US Food and Drug Administration (FDA)-approved to promote the healing of ulcers that have failed standard wound care. Constructed by culturing human foreskin-derived neonatal fibroblasts in a bovine type I collagen matrix over which human foreskin-derived neonatal epidermal keratinocytes are then cultured and allowed to stratify, Apligraf provides both cells and matrix for the nonhealing wound.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(148 citation statements)
references
References 37 publications
(39 reference statements)
1
135
0
6
Order By: Relevance
“…Apligraf (Organogenesis Inc., Canton, MA, USA), is a bilayered bioengineered skin substitute (BBSS) containing a dermal layer of human fibroblasts in a bovine type I collagen lattice and an epidermal layer formed by human keratinocytes (25)(26)(27)(28). Neonatal human foreskin is the source for the fibroblasts and keratinocytes, and Apligraf is FDA approved for treatment of partial & full-thickness skin ulcers due to venous insufficiency and DFU that have not appropriately responded to conventional therapy.…”
Section: Human Skin Allografts and Bioengineered Skin Substitutesmentioning
confidence: 99%
“…Apligraf (Organogenesis Inc., Canton, MA, USA), is a bilayered bioengineered skin substitute (BBSS) containing a dermal layer of human fibroblasts in a bovine type I collagen lattice and an epidermal layer formed by human keratinocytes (25)(26)(27)(28). Neonatal human foreskin is the source for the fibroblasts and keratinocytes, and Apligraf is FDA approved for treatment of partial & full-thickness skin ulcers due to venous insufficiency and DFU that have not appropriately responded to conventional therapy.…”
Section: Human Skin Allografts and Bioengineered Skin Substitutesmentioning
confidence: 99%
“…Apligraf ® is supplied as needed, in one size, with a shelf-life of 10 days. It was FDA-approved in 1998 for use in conjunction with compression therapy for the treatment of non-infected, partial-and full-thickness skin ulcers [26].…”
Section: Apligraf ® (Organogenesis)mentioning
confidence: 99%
“…Research in this field is currently flourishing, and each month brings its lot of newly demonstrated capacity for differentiation. For skin grafting, current techniques provide essentially two types of cells, basal keratinocytes for epidermis and fibroblasts for dermis [32]. The host provides additional migratory cells, in particular monocyte-derived Langerhans cells and blood vessels-forming cells.…”
Section: What Can Pluripotent Stem Cells Do For Our Skin Beyond Keratmentioning
confidence: 99%